Membaca dan Menafsir Kejadian 1:26-28 dalam Fungsi Kosmis Budaya Toraja untuk Membangun Paradigma Misi Kontekstual-Ekologis - Gayus Darius (Melo: Jurnal Studi Agama-agama, 2022)
Abstract: The mission perspective developed over the years which is anthropocentric in nature indirectly legitimizes the massive exploitation of nature which causes environmental damage. This departs from a human desire to lead to prosperity and prosperity by increasing economic production. However, what has happened has resulted in inequality and sustainable natural damage. The research will focus on reinterpreting Genesis 1:26-28 from the perspective of the cosmic function of Toraja culture to build a contextual-ecological mission paradigm. So that nature is seen in a different way and treated as it should be. This research will use descriptive qualitative method with text analysis approach and tenography. The end of this study shows that the cosmic function of Toraja culture and the reinterpretation of the text of Genesis 1:26-28 have similarities by viewing that other creations are human brothers and are one unified whole, so they are called sangserekan. It brings awareness of a new missionary paradigm that nature or cosmic is part of Christ's redemptive design. The mission paradigm that had been built up from the West then slowly shifted from ecclesiastical to theocentric. From an organizational church to an organismic church.